Al-Jazeera, Qatar, and New Tactics in State-Sponsored Media Diplomacy. (September 2013) - Samuel-Azran, Tal
The use of international broadcasting, a tool of public diplomacy since World War I, can be divided into two chronological periods. The first, which began during World War I and declined in the post–Cold War era, was characterized by international government-sponsored radio broadcasters. The second began with the emergence of privately owned global news networks (e.g., CNN, Sky News, and MSNBC) in the 1980s and 1990s, which were deemed more credible than government-sponsored stations. Based on an 8-year study of Al-Jazeera's coverage of Saudi affairs throughout the Qatari–Saudi conflict, which revealed a strong correlation between Al-Jazeera Arabic's tone toward Saudi affairs and the development of the Qatari–Saudi conflict, the article argues that Qatar invented a new model of public diplomacy by operating Al-Jazeera as a hybrid state-sponsored/private network, effectively transforming the network into a highly potent public diplomacy tool. Accordingly, the article discusses the interplay among news networks, ownership, and use of public diplomacy tactics in contemporary international broadcasting.